Dopant profiles in silicon created by MeV hydrogen implantation: Influence of annealing parameters - Laven, Johannes; Hans Joachim, Schulze; Häublein, Volker; Niedernostheide, Franz Josef; Ryssel, Heiner; Frey, Lothar (Physica Status Solidi (C) Current Topics in Solid State Physics, 2011)
Dopant profiles created by MeV proton implantation in float zone and Czochralski silicon are examined with spreading resistance probe measurements after annealing in the temperature range of 300–500 °C. For the description of the profile shape, two species are used, one being the implanted and mobile hydrogen and the other being an immobile irradiation induced point defect complex. The diffusion of the implanted hydrogen through the radiation damaged layer is found to be of great relevance for the resulting depth distribution of the hydrogen related donors. An effective diffusion coefficient is given for implantation into float zone silicon. Furthermore, the profile shape varies significantly with the annealing temperature. It is proposed that two donor species are generated which each exhibit a different thermal stability, and that these two species have individual depth distributions. Profiles created in Czochralski silicon seem to be additionally affected by an enhanced generation of oxygen thermal donor species.